Information Age Reform of the Public Sector: The Potential and Problems of IT for India - RICHARD HEEKS (1998)
As in many countries, public sector reform in India has consisted of five main components: increased efficiency, decentralisation, increased accountability, improved resource management, and marketisation. `Information age reform' means delivering these ongoing reform components with a more overt role for information and with greater use of information technology. A review of global experience suggests that information age reform has great potential to improve public administration and other components of the public sector. However, the Indian reality - like that for many developing countries - has been more problematic, with many failures of such reform; failures that can be described as total, partial or failures of sustainability and replication. The explanation for such failure lies partly in the approach to reform adopted by senior public officials. A `four Is' model of approaches is described: the pre-information age approach of `ignore', and the information age approaches of `isolate', `idolise' and `integrate'. Analysis of Indian cases suggests it is the last approach that is most likely to deliver reform objectives; yet it remains the least commonly-adopted. Changes are therefore required in current strategies for public administration training and the management of change. Such findings will hold true for many other developing countries